2022
DOI: 10.1002/jcsm.13024
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of phosphatidylserine receptors in the skeletal muscle regeneration: therapeutic implications

Abstract: Sarcopenia is a progressive loss of muscle mass and strength with a risk of adverse outcomes such as disability, poor quality of life, and death. Increasing evidence indicates that diminished ability of the muscle to activate satellite cell-dependent regeneration is one of the factors that might contribute to its development. Skeletal muscle regeneration following myogenic cell death results from the proliferation and differentiation of myogenic stem cells, called satellite cells, located beneath the basal lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 126 publications
0
11
0
Order By: Relevance
“…Bone marrow-derived monocytes very often appear and differentiate into macrophages in tissues where an increased rate of cell death occurs, such as during skeletal muscle injury [ 54 ] or in the case of high fat diet-induced death of adipocytes [ 55 ]. Thus, a retinoid-induced increase in their efferocytosis capacity will contribute to the efficient clearance of dead cells in these tissues to prevent chronic inflammation and the development of autoimmunity [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow-derived monocytes very often appear and differentiate into macrophages in tissues where an increased rate of cell death occurs, such as during skeletal muscle injury [ 54 ] or in the case of high fat diet-induced death of adipocytes [ 55 ]. Thus, a retinoid-induced increase in their efferocytosis capacity will contribute to the efficient clearance of dead cells in these tissues to prevent chronic inflammation and the development of autoimmunity [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that cell proliferation was promoted via activation of JNK [ 48 , 49 ]. Similar to this, it has been shown that ERK activation mediates cell proliferation and cell cycle progression in myoblasts [ 50 ], and early ERK signal was a crucial factor in determining the proliferation of muscle stem cells [ 51 ]. These results suggested that the proliferation of porcine skeletal muscle cells was regulated by MAPK signaling pathway after overexpression of GPX2 .…”
Section: Discussionmentioning
confidence: 67%
“…In addition, enveloped viruses and liposomes exposing PtdSer promote syncytium formation 174 , supporting that extracellular PtdSer promotes cell fusion. The involvement of various PtdSer-recognition systems has been proposed for the fusion process, but how they work remains elusive 128,175,176 .…”
Section: Ptdser In Cell Fusionmentioning
confidence: 99%